Delay-adjusted age- and sex-specific case fatality rates for COVID-19 in South Korea: Evolution in the estimated risk of mortality throughout the epidemic - Newall, A.T. (Int J Infect Dis, 2020)
OBJECTIVES: The aim of this study was to estimate delay-adjusted case fatality rates (CFRs) for COVID-19 in South Korea, and evaluate how these estimates have evolved over time throughout the epidemic. METHODS: Public data from the Korea Centers for Disease Control and Prevention (KCDC) were used to estimate age- and sex-specific CFRs for COVID-19 in South Korea up to June 12, 2020. We applied statistical methods previously developed to adjust for the delay between diagnosis and death, and presented both delay-adjusted and crude (unadjusted) CFRs throughout the epidemic. RESULTS: The overall estimated delay-adjusted CFR was 2.39% (3.05% for males and 1.92% for females). Within each age strata where deaths were reported, males were found to have significantly higher CFRs than females. The estimated CFRs increased substantially from age 60 years in males and from 70 years in females. Both the delay-adjusted and crude CFRs were found to have evolved substantially, particularly early in the epidemic, converging only from mid-April 2020. CONCLUSIONS: The CFRs for South Korea provide an estimate of mortality risk in a setting where case ascertainment is likely to be more complete. The evolution in CFRs throughout the epidemic highlights the need for caution when interpreting CFRs calculated at a given time point.